Who knows what when? The Information content of pre-IPO market prices - Gunter Löffler; Patrick F. Panther; Erik Theissen (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
To resolve the IPO underpricing puzzle it is essential to analyze who knows what when during the issuing process. In Germany, broker-dealers make a market in IPOs during the subscription period. We examine these pre-issue prices and find that they are highly informative. They are closer to the first price subsequently established on the exchange than both the midpoint of the bookbuilding range and the offer price. The pre-issue prices explain a large part of the underpricing left unexplained by other variables. The results imply that information asymmetries are much lower than the observed variance of underpricing suggests.
urn:nbn:de:hebis:30-18327
Keywords: G10; G14; G24; 330; Initial public offerings; asymmetric information; information production; underpricing; when-issued trading; winner's curse; Emissionskurs; Börsengang; Wertpapierhandel; Asymmetrische Information; Schätzung; Deutschland